Hopsalot's Garden - Weinberger, Kimberly (New York : Scholastic, 2000)
When Hopsalot, the rabbit, plants his seeds in the spring, his garden is surpassed by those of his friends, but he must wait until fall to find out why.
"Based on the #1 educational software for children"
Keywords: Gardens -- fiction; Rabbits -- fiction; Seasons -- fiction